The chemical and microbiological quality of pastrami produced by using various salting techniques and kept at+4°c - Ümit Gürbüz; Yusuf Doğruer; Nazif Anıl (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the effects of various salting techniques (dry, dipping and injektion) on physicochemical and microbiological properties of pastrami during storage periods (60 days, +4 °C). At the begining of the storage periods, moisture contents, salt contents, pH and water activity (aw ) values of pastrami samples applied dry, dipping and enjection techniques were respectively detected 42.65 - 43.36 and 45.16 %; 7.47, 8,58 and 6,18 %, 5.70, 5.46 and 5.97; 0.85, 0.86 and 0,88, During storage periods significiant decreaments in the moisture contents of pastrami samples applied various sailing techniques aw observed because of drying effects in moisture contents. Parallely, Water activity (aw) values of pastrami samples were decressed and salt content of pastrami samples were increased. During this period, the difference pH values of pastrami samples among the groups were not faund to be significant.There was no significant differences in the number of microorganizms (total count .Staphylococcus-micrococcus, Lactobacillus, mold and yeast) of the samples among the groups at the 60th day of the experiment. It was concluded that depending upon salting techniques the pastramies loasing chewing properties became dry and salting because of significant decreament in moisture contents and increaments in salt contents at the end of the storage period.